THE EFFECT OF DIGITAL MARKETING, SERVICE QUALITY AND ELECTRONIC WORD OF MOUTH (E-WOM) ON REPURCHASE INTEREST IN LUNA CHICKEN CUTTING HOUSE UMKM - Adrian Fahrozi; Wisnu Setiazid Sinaga; Willy Cahyadi (CV. Radja Publika, 2025)
This study aims to analyze the effect of digital marketing (X1), service quality (X2) and electronic word of mouth (E-WOM) (X3) on repurchase interest (Y) at the Luna broiler chicken UMKM. The method used is quantitative by distributing questionnaires filled out by 96 respondents selected using accidental sampling techniques in the period December 2024 to January 2025. The results of the analysis show that both X variables have a positive and significant effect on variable Y, where digital marketing, service quality and electronic word of mouth can increase repurchase interest at the Luna broiler chicken house. Validity and reliability tests state that the questionnaire instrument used has a good level of validity and reliability. The coefficient of determination test shows that both X variables are able to contribute to variable Y. The results of the study are consistent with the theory that states that digital marketing (X1), service quality (X2) and electronic word of mouth (X3) are important factors that influence repurchase interest (Y). Keywords: Author Guidelines; Al-Kharaj Journal; Article Template